Aplicación móvil para el manejo adecuado de técnicas manuales de instrumentación de endodoncia - Sierra Claro, Adriana Del Pilar; Peñaranda Granados, Edy Johana (Universidad Antonio Nariño, 2021)
The availability of new technologies improves accessibility to the web, ensuring that information management is carried out with immediacy, complementing and facilitating the study processes Objective: Design a mobile dental application for the proper management of manual instrumentation techniques in endodontics. Materials and methods: The research was made known in a virtual way, with a survey and delivery of a consent, identifying the weaknesses in the management of manual instrumentation techniques, complementing with an educational manual that presents a technical language that guarantees students reliability in information. The mobile application is configured with the Kotlin program developed in the Android Studio environment; finally, the instructions were designed as a guide for handling the mobile application. Results: As a final result of the project, a mobile application "Endodontics" was made, which was executed based on an educational manual on manual instrumentation techniques, in turn, an instruction was developed that allows the user to understand the operation and management of the application.